Analysis Of Water Harvester Machine Performance Using Single-Sided Thermoelectric Cooling - Rezki, Dedi Nur; Rahman, Jhonni (Jurnal Teknik Mesin, 2024)
This study addresses the urgent issue of global water scarcity, particularly in arid regions with limited access to conventional water sources. The performance of a water harvester equipped with single-sided thermoelectric cooling technology is evaluated to enhance water collection efficiency from the atmosphere. The primary objective of this research is to optimize the machine's performance by varying fan speeds and analyzing its impact on collected water volume. The methodology involves experiments conducted at three different fan speeds: 1000 RPM, 1500 RPM, and 2000 RPM, with each speed tested for three hours and data collected every 30 minutes. The observed variables include collected water volume, air temperature, and humidity. Results indicate that water collection efficiency increases with higher fan speeds, with 2000 RPM yielding the highest volume. However, efficiency declines after 90 minutes, mainly influenced by fluctuating external factors such as temperature and humidity. Additionally, increased fan speeds may result in higher energy consumption, which is a consideration for developing more energy-efficient machines. The study recommends further development to integrate automatic control systems capable of adjusting fan speeds based on environmental changes in temperature and humidity. The conclusion of this research is that thermoelectric cooling technology has significant potential for water harvesting, yet sustainable innovations are necessary for adaptation across diverse environmental conditions.